Trends in Factors Affecting Pregnancy Outcomes Among Women With Type 1 or Type 2 Diabetes of Childbearing Age (2004–2017) - Gaudio, Mariangela; Dozio, Nicoletta; Feher, Michael; Scavini, Marina; Caretto, Amelia; Joy, Mark; Van Vlymer, Jeremy; Hinton, William; de Lusignan, Simon (Frontiers in Endocrinology, 2021)
Aim: To describe trends in the management of women with diabetes from an English primary care perspective. Methods: We identified women with diabetes aged 16-45 years from the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network, an English primary care sentinel database. Repeated annual cross-sectional analyses (2004-2017) assessed the prevalence of unfavourable factors for pregnancy, such as obesity, poor glycaemic control, microalbuminuria, hypertension, use of medications for treating diabetes and comorbidities and not recommended for pregnancy. Results: We identified 3,218 women (61.5% with Type 2 diabetes) in 2004 and 6,657 (65.0% with Type 2 diabetes) in 2017. The proportion of women with ideal glycaemic control for conception (HbA1c≤ 6.5%) increased over time, in patients with Type 1 diabetes from 9.0% (7.1-11.0%) to 19.1% (17.2-21.1%), and in those with Type 2 diabetes from 27.2 % (24.6-29.9% ) to 35.4% (33.6-37.1%). The proportion of women with Type 2 diabetes prescribed medications different from insulin and metformin rose from 22.3% (20.5-24.2%) to 27.3% (26.0-28.6%). In 2017, 14.0% (12.6-15.4%) of women with Type 1 and 30.7% (29.3-32.0%) with Type 2 diabetes were prescribed angiotensin modulating antihypertensives or statins. We captured at least one unfavourable factor for pregnancy in 50.9% (48.8-52.9%) of women with Type 1 diabetes and 70.7% (69.3-72.0%) with Type 2 diabetes. Only one third of women with Type 1 diabetes (32.2%, 30.3-34.0%) and a quarter of those with Type 2 diabetes (23.1%, 21.9-24.4%) were prescribed hormonal contraception. However, only in women with Type 1 diabetes the prescription of contraception was higher among those with unfavourable factors for pregnancy compared to those without unfavourable factors. Conclusions: Despite significant improvements in general diabetes care, the majority of women with Type 1 or Type 2 diabetes have unfavourable, although mostly modifiable factors for the start of pregnancy. Good diabetes care for women of childbearing age should include taking into consideration a possible pregnancy.